Mother Mary comes to me - Roy, Arundhati (India : Penguin Random House, 2025)
"Legendary and beloved novelist Arundhati Roy’s memoir, tracing her complicated relationship with her mother and her literary and political becoming."--
ENH
Issued also in electronic format.
Book Finder International
Keywords: Roy, Arundhati; Authors, Indic -- 20th century -- Biography; Authors, Indic -- 21st century -- Biography; Political activists -- India -- 21st century -- Biography; Mothers and daughters -- Biography; Écrivains de l'Inde -- 20e siècle -- Biographies; Écrivains de l'Inde -- 21e siècle -- Biographies; Activistes -- Inde -- 21e siècle -- Biographies; Mères et filles -- Biographies; Autobiographies